2012
DOI: 10.1016/j.jcv.2012.01.017
|View full text |Cite
|
Sign up to set email alerts
|

Heterosexual transmission of human immunodeficiency virus type 1 subtype C in southern Brazil

Abstract: The molecular epidemiology of HIV-1 in the southernmost Brazil is currently steady with predominance of HIV-1C. This is the first study showing a robust association of the infection by this subtype and heterosexual transmission in the state of Rio Grande do Sul, Brazil.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 37 publications
4
21
0
3
Order By: Relevance
“…[8][9][10][11][12][13][14][15][16] In the city of Rio Grande, one of the foci of this study, such an increase is clearly evident: from 22% in 2002 to 56% in 2010. 16,17 The introduction of highly active antiretroviral therapy (HAART) in HIV-infected patients is associated with a marked reduction in morbidity and mortality. 18,19 Resistance to antiretroviral (ARV) drugs is a major cause of treatment failure and has been associated with higher mortality rates.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…[8][9][10][11][12][13][14][15][16] In the city of Rio Grande, one of the foci of this study, such an increase is clearly evident: from 22% in 2002 to 56% in 2010. 16,17 The introduction of highly active antiretroviral therapy (HAART) in HIV-infected patients is associated with a marked reduction in morbidity and mortality. 18,19 Resistance to antiretroviral (ARV) drugs is a major cause of treatment failure and has been associated with higher mortality rates.…”
Section: Introductionmentioning
confidence: 79%
“…Primers and PCR conditions for both reactions have been previously described. 14,16,28 Purified PCR products were sequenced with the Prism Ò BigDyeÔ Terminator Cycle Sequencing Ready Reaction Kit (Thermo Scientific, Carlsbad, USA) using the inner primers of each respective PCR reaction. DNA sequencing was carried out in an automated ABI 3130XL Genetic Analyzer (Thermo Scientific).…”
Section: Study Subjects and Sample Collectionmentioning
confidence: 99%
“…In addition, in Guinea-Bissau, infection with recombinant A3/02 was associated with increased risk of AIDS or death compared with subtype A3 (14). There is also evidence for reduced subtype C Gag-protease function relative to subtype B, corresponding with slower disease progression in subtype C-infected individuals; in Brazil, where subtype C cocirculates with subtypes B and F1 and intersubtype recombinants, subtype C was associated with higher CD4 counts (18). However, there are conflicting reports of the disease progression rate of subtype C relative to that of subtypes A and D (12,(15)(16)(17)59).…”
Section: Discussionmentioning
confidence: 99%
“…There is also evidence that recombinant forms have a higher rate of progression to AIDS than does subtype A (10,14), although this was not observed in another study (12). There are conflicting reports regarding the rate of disease progression of subtype C relative to that of other subtypes (12,(15)(16)(17)(18). While there is general agreement that subtype C has a transmissibility rate at least equal to those of other M group subtypes (19,20), some studies have reported increased transmissibility of subtype C compared to subtypes A and D (21)(22)(23).…”
mentioning
confidence: 99%
“…Whereas in POA, the association between men having sex with men (MSM) and HIV-1B disappeared in more recent sampling because of an expansion of HIV-1C in heterosexual (HET) and MSM groups (45), compartmentalized epidemics are still observed in other cities in the southern region, including Paraná, which could be explained by later introduction of HIV-1C (4,(46)(47)(48).…”
Section: Discussionmentioning
confidence: 99%